The Secondary Metabolites and Biosynthetic Diversity From Aspergillus ochraceus - Chen, Lin; Li, Erfeng; Wu, Wenqing; Wang, Gang; Zhang, Jiaqian; Guo, Xu; Xing, Fuguo (Frontiers in Chemistry, 2022)
Aspergillus ochraceus, generally known as a food spoilage fungus, is the representative species in Aspergillus section Circumdati. A. ochraceus strains are widely distributed in nature, and usually isolated from cereal, coffee, fruit, and beverage. Increasing cases suggest A. ochraceus acts as human and animal pathogens due to producing the mycotoxins. However, in terms of benefits to mankind, A. ochraceus is the potential source of industrial enzymes, and has excellent capability to produce diverse structural products, including polyketides, nonribosomal peptides, diketopiperazine alkaloids, benzodiazepine alkaloids, pyrazines, bis-indolyl benzenoids, nitrobenzoyl sesquiterpenoids and steroids. This review outlines recent discovery, chemical structure, biosynthetic pathway and bio-activity of the natural compounds from A. ochraceus.